The Relationship of Mother's Knowledge with Stunting Incidents in Children Aged 0 - 59 Months - Zakiyah, Zakiyah; Sari, Anggi Maulida; Damayanti, Siti (Institute Of Computer Science (IOCS), 2024)
Stunting is a growth and development disorder due to lack of nutritional intake, recurrent infections characterized by body length or height below standard. Toddlers with stunting will have a lower level of intelligence, be susceptible to disease and delayed mental development. The aim of this research is to determine the relationship between maternal knowledge and the incidence of stunting in children aged 0-59 months in the Meureubo Health Center Working Area, West Aceh Regency. The method used is observational with a cross sectional research design. The population in this study were mothers who had toddlers aged 0-59 months in the Meurebo Health Center Working Area, West Aceh district, totaling 2296 people. Determining the number of samples used the Slovin formula with the Stratified Random Sampling technique, totaling 95 people. Data was collected using a questionnaire to measure maternal knowledge and anthropometry to measure body height. Determining whether or not there is stunting is assessed using the child's Z-Score standard. In this study, univariate analysis was carried out which was presented in the form of a frequency distribution table. Next, bivariate analysis was carried out between the two variables using the Chi Square statistical test. Results The chi square test shows that maternal knowledge (0.000) is related to stunting in toddlers. It is hoped that the Meureubo Community Health Center will further improve health promotion in the form of education regarding the causes and prevention of stunting.